Analysis of the Application of Project Based Learning on the Material of Atmospheric Layers at SMAN 11 Medan Class X in the Independent Curriculum - Aulia, Vina; Zuhrika, Dhea; Barus, Mita Nalsalisa Br; Andini, Sri; Hutasuhut, Vadillah Raihto; Yuniastuti, Eni (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research analyzes the implementation of Project Based Learning (PjBL) in teaching atmospheric layers to tenth-grade students at SMAN 11 Medan within the context of the Merdeka Curriculum. Through a qualitative approach utilizing observation, interviews, and documentation methods, this study explores the effectiveness of PjBL in enhancing students' understanding of atmospheric concepts. The findings indicate that PjBL implementation through the creation of atmospheric layer miniatures and direct observation-based learning effectively increases student participation and comprehension. Learning is conducted in group systems to optimize resources and encourage student collaboration. Learning evaluation is carried out through daily assessments, both oral and written. The main challenge identified is the varying levels of understanding among students, particularly between advanced and regular classes. This research recommends developing learning differentiation strategies, enhancing teacher competency in PjBL implementation, and integrating digital technology to optimize atmospheric learning within the Merdeka Curriculum framework.